The Issue of Vision By Ahmed Al Manjour - Yahya Ben Abdelouahab (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Islamic methodological approach to thinking and deriving evidence through argumentation and logical principles has been highlighted. Muslims, especially Moroccans, haven't solely relied on traditional evidence to establish beliefs and respond to opponents. They have also bolstered their perspectives with rational evidence, excelling in this regard. Ahmed al-Manjour, through the manuscripts we studied in this paper, revealed the vast array of rational methods he employed to defend prevalent beliefs in Morocco. This includes the freedom of thought, creativity, and classification that prevailed during the Saadi dynasty in Morocco. For al-Manjour, the matter of